The Effectiveness of Red Piper Crocatum as a Natural Antiseptic in Reducing Fluor Albus Symptoms in Women of Reproductive Age - Wulandari, Endah Sri; Angesti, Herlina Puji (Jurnal Ilmu Kesehatan dan Kesehatan, 2025)
One of the most common reproductive health issues experienced by women is Fluor Albus (vaginal discharge). In general, women with fluor albus produce excessive mucus accompanied by an unpleasant odor. This study aims to analyze the effect of boiled Red Piper crocatum as a natural antiseptic on the reduction of Fluor Albus symptoms in women of reproductive age in Sidodadi Village, Sukosewu Subdistrict, Bojonegoro Regency. This research employed a pre-experimental design method, utilizing a one-group pre-test and post-test approach. The population consisted of 32 respondents, all of whom were included in the sample using a total sampling technique. Data were analyzed using a paired t-test. The results showed a p-value of 0.000, indicating that p < 0.05, and therefore, the alternative hypothesis (H₁) was accepted. This means that boiled Piper Crocatum significantly reduces Fluor Albus symptoms in women of reproductive age in Sidodadi Village, Sukosewu Subdistrict, Bojonegoro Regency. Conclution of this study Maintaining the normal flora of the vagina can be supported by using boiled Red Piper Crocatum water to reduce pathological vaginal discharge symptoms, due to its clinically proven active compounds.